Development and Preliminary Testing of a Computerized Animated Activity Questionnaire in Patients With Hip and Knee Osteoarthritis. Issue 1 (January 2015) - Peter, W. F.; Loos, M.; de Vet, H. C. W.; Boers, M.; Harlaar, J.; Roorda, L. D.; Poolman, R. W.; Scholtes, V. A. B.; Boogaard, J.; Buitelaar, H.; Steultjens, M.; Roos, E. M.; et al.
<x xml:space="preserve">Abstract</x> Objective To develop an Animated Activity Questionnaire (AAQ) based on video animations for assessing activity limitations in patients with hip/knee osteoarthritis (OA) that combines the advantages of self‐reported questionnaires and performance‐based tests without many of their limitations and to preliminarily assess its reliability and validity. We hypothesized that the AAQ would correlate highly with performance‐based tests and moderately with self‐reported questionnaires. Methods Item selection was based on the pilot AAQ, prespecified conditions, the International Classification of Functioning, Disability, and Health core set for OA, existing measurement instruments, and focus groups of patients. Test–retest reliability was assessed in 30 of 110 patients. In 110 patients, correlations were calculated between the AAQ and the self‐reported Hip Disability/Knee Injury and Osteoarthritis Outcome Score activities of daily living subscale (H/KOOS). In 45 of 110 patients, correlations with performance‐based tests (stair climbing test, timed up and go test, and 30‐second chair stand test) were calculated. Results In total, 17 basic daily activities were chosen for the AAQ. Video animations were made showing a person performing each activity with 3–5 different levels of difficulty. Patients were asked to select the level that best matched their own performance. Reliability was high (intraclass correlation coefficient 0.97 [95% confidence interval 0.93–0.98]); the AAQ correlated highly with performance‐based tests (0.62), but higher with the H/KOOS (0.76) than expected. Conclusion A computerized AAQ for assessing activity limitations was developed. Content validity was considered good. Preliminary validation results showed high reliability, but construct validity needs further study with a larger sample size. Continuing research will focus on construct validity and crosscultural validity.